A Noble Security Analysis of Various Distributed Systems - Akter, Sworna; Hossain, Md. Alamgir; Rahman Redoy Akanda, Md. Mojibur (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
Distributed systems increased the performance of a system by allowing applications to be processed in parallel. It helps us to share resources like printers, computers, storage facilities, data, files, web pages, networks, and thus it reduces the cost by shaing a single resource among several users instead of multiple resources. Since multiple machines communicate with each other through the network so they can be easily affected by the attacker and the full system should be corrupted. Users can access remote and local resources but they also may not aware of which machines their processes are running on. So, secure communiction of a distributed system is the most important issue. We need to analyze various vulnerabilities and can take proper protection of the system. In this paper, we discuss different architectural styles of distributed systems. Also, hold up different threads and protection mechanisms to get rid of these threads. The most focusing part of this paper is a summary of various distributed systems security. Here we hold up different distributed system security techniques like SSSE algorithm, BLCS architecture, ODIS algorithm, two eavesdropper model, dynamic cuckoo filter, etc. Finally, we summarize the full discussion like used methodology or architecture, advantages, disadvantages, accuracy, and future work in a table by which an author can easily gather knowledge about the summary of this paper. To better understanding, we show the result of various papers with a visual representation. I think it helps authors to know about security techniques and grow interested to work in this area.